A Researcher's Guide to Metadata Integration Increasing Discoverability of African Research - CLARK, ROSA; Collins, Susan; Fairhurst, Vanessa; Kemp, Jennifer; Obanda, Johanssen; Owango, Joy; van Zyl, Kylie (My University, 2022)
Crossref, AfricArxiv, and the Training Centre in Communication (TCC Africa) joined forces to host a series of workshops aimed at supporting discoverability or research in Africa through metadata and integrations between repositories and indexing platforms.
PART I The first session was held on 21st April 2022 and covered the topic: Who Crossref is, what they do for the benefit of the scholarly community. https://africarxiv.pubpub.org/pub/qkuvlthx#nqgwkvav8iy Part II The second session held on 28th April 2022, featured a presentation from Jennifer Kemp, Head of Partnership at Crossref on How Crossref metadata integrates with scholarly research tools and discovery systems. https://africarxiv.pubpub.org/pub/qkuvlthx#nywb358xggi Part III The last part of the series was held on 5th May 2022, on the topic “How members work with Crossref to register research content” presented by Susan Collins- Community Engagement Manager at Crossref. The session also featured a presentation by Kylie van Zyl- Journal Assessment Officer at African Journal Online(AJOL) who guided the participants on Crossref DOI’s at AJOL. https://africarxiv.pubpub.org/pub/qkuvlthx#nu4zo0rsceq
Keywords: Metadata Integration; African Research; AfricArxiv